2012
DOI: 10.1186/1687-6180-2012-111
|View full text |Cite
|
Sign up to set email alerts
|

Sparse covariance fitting for direction of arrival estimation

Abstract: This article proposes a new algorithm for finding the angles of arrival of multiple uncorrelated sources impinging on a uniform linear array of sensors. The method is based on sparse signal representation and does not require either the knowledge of the number of the sources or a previous initialization. The proposed technique considers a covariance matrix model based on overcomplete basis representation and tries to fit the unknown signal powers to the sample covariance matrix. Sparsity is enforced by means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…In array processing a narrowband signal is usually defined as a signal that meets the condition about the bandwidth to center frequency being less than 1% [16], [17]. Here we extend the narrowband model from [10], [11] to a wideband model and derive a new wideband direction of arrival estimation method which is the novelty of this paper. The received wideband signal is first decomposed into a set of independent narrowband signals using Discrete Fourier Transform (DFT) ( [2], [3]) or narrowband filters ( [6]).…”
Section: This Paper Is a Revised And Expanded Version Of The Paper Prmentioning
confidence: 99%
See 1 more Smart Citation
“…In array processing a narrowband signal is usually defined as a signal that meets the condition about the bandwidth to center frequency being less than 1% [16], [17]. Here we extend the narrowband model from [10], [11] to a wideband model and derive a new wideband direction of arrival estimation method which is the novelty of this paper. The received wideband signal is first decomposed into a set of independent narrowband signals using Discrete Fourier Transform (DFT) ( [2], [3]) or narrowband filters ( [6]).…”
Section: This Paper Is a Revised And Expanded Version Of The Paper Prmentioning
confidence: 99%
“…In order for (10) to be well defined, we need the value of U to be dependent on the variance of the term has correlated entries, it is very difficult to predict the value of U in (11). But using the estimate of the decorrelation…”
Section: This Paper Is a Revised And Expanded Version Of The Paper Prmentioning
confidence: 99%
“…SSR based on an 2,0 mixed-norm approximation has been considered in [38], while a convex relaxation approach based on the 2,1 mixed-norm has been proposed in [37]. DOA estimation based on secondorder signal statistics has been addressed in [42], [43], where a sparse covariance matrix representation is exploited by application of a sparsity prior on the source covariance matrix, leading to an SMV-like sparse minimization problem. In [44]- [46] the authors propose the SPICE method, which is based on weighted covariance matching and constitutes a sparse estimation problem which does not require the assumption of a sparsity prior.…”
Section: Introductionmentioning
confidence: 99%
“…For example, [11] proposes the idea that the eigenvectors of the array covariance matrix have a sparse representation over a dictionary constructed from the steering vectors. In [12,14], it is shown that when the received signals are uncorrelated, the array covariance matrix has a sparse representation over a dictionary constructed using the atoms, i.e. the correlation vectors.…”
Section: Introductionmentioning
confidence: 99%